Considerations on the influence of the implementation of the Bariri Hydroelectric Power Plant on the landscape of the Tietê River. - Chiari , Karina Cristina; Constantino , Norma Regina Truppel (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The landscape is a living record of a region's history and culture. In this sense, studying it makes it possible to understand how people interact with the environment and how societies have adapted and shaped the landscape over time. Thus, the core purpose of this work is to make considerations and analyze the transformations that occurred in the landscape of the Tietê River after the implementation of the Bariri Hydroelectric Power Plant.The methodology is based on the study of the landscape and brings Besse (2014) as a theoretical reference, where the objectives will be achieved through the bibliographic and documentary survey, fostering the theoretical basis of the history of the city and the territory. Landscape studies are critical to the understanding and proper management of the natural and built environment, as they provide crucial information for conservation, urban planning, the protection of cultural heritage, and the promotion of people's quality of life and well-being. As a result, the article presents a brief history of the transformations that occurred in the Tietê River after the implementation of the Bariri Hydroelectric Power Plant and exposes what these transformations caused to the environment and the population of the region. This work contributes to the ongoing research with the Graduate Program in Architecture and Urbanism of the Faculty of Arts, Communication and Design, of the State University "Júlio de Mesquita Filho" – UNESP.
Keywords: Landscape; Tietê River; Barrage